The political economy of domestic resource mobilization in Nicaragua: Changing state-citizen relations and social development - Gloria Carrión (United Nations Research Institute for Social Development (UNRISD), 2019)
Nicaragua has gone through profound political, economic and social transitions in recent decades. Following a turbulent history of dictatorship (Somoza 1936-1979), the Sandinista revolution (1979-1989) and neoliberal adjustment (1990-2006), it remains one of the poorest countries in Latin America, second only to Haiti. Periods of high social tension and violence were followed by relative peace and democratic transitions. Social conflicts and contradictions, however, have continued to emerge. These dynamics have circumscribed strategies for mobilizing financial resources for development. In 2007, the Sandinistas (Frente Sandinista de Liberación Nacional - FSLN) returned to power continuing the economic liberalization policies of former neoliberal governments, directly contradicting the policy stance the FSLN had pursued in the 1980s. While president Ortega achieved some successes regarding the economy as a result of the implementation of several social and economic empowerment and food security programmes, major challenges remain, particularly in areas like civil society participation, institutional building, human rights, and democratization. This paper shows that when strong state-society relations are fostered; effective bargaining and inclusive participation of civil society in social policy making and spending occurs; the state secures mechanisms to prevent elite capture of resources; civil society successfully mobilizes and negotiates with the state regarding the distribution of revenues from extractive industries; and democratization and institution building processes are strengthened, social policy spending tends to increase and expand. In Nicaragua, distinct political periods are associated with different strategies and outcomes regarding both social spending and mobilization of fiscal revenues. The extent to which these strategies have positively impacted social development show important links with the quality of state-society relations.
Keywords: 330